Analisis Pengaruh Motivasi dan Tingkat Pendidikan terhadap Kepatuhan Wajib Pajak - Yessy Elizabeth Sianturi; Dian Efriyenti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Tax is phenomenon Which continue develop. Wrong One many business Which used government for reach independence nation and country in financing development Which beneficial for well-being general is taxation. Level obedience must tax Of Batam relatively low like seen on table Of above. Matter This caused although amount WP registered each the year increase, Lots must tax Which register but No convey Letter Announcement Yearly (SPT). increasing obedience must tax care obligation tax is task Which difficult. On research is plan work Which arranged regularly comprehensive in relation with connection between variable, possible findings study for fulfil question study. Research is conducted on a sample, and descriptive statistics can be used to analyze it if the research only needs to present sample data and does not wish to draw conclusions from the population it is sampled from. This study used descriptive testing with several tests carried out using the SPSS 26 program. The results of this study showed that the motivation variable had a significance value of 0.000 and the Education Level Variable (X2) had a significance value of 0.007, this value is less than 0.05 (0.000 < 0 , 05). This means H1 and H2 are accepted. So it can be concluded that motivation (X1) and education level (X2) partially have a significant effect on taxpayer compliance.